Methanol‐driven enhanced biological phosphorus removal with a syntrophic consortium. Issue 2 (17th August 2012) - Tayà, Carlota; Guerrero, Javier; Vanneste, Gianni; Guisasola, Albert; Baeza, Juan A.
Abstract: The presence of suitable carbon sources for enhanced biological phosphorus removal (EBPR) plays a key role in phosphorus removal from wastewater in urban WWTP. For wastewaters with low volatile fatty acids (VFAs) content, an external carbon addition is necessary. As methanol is the most commonly external carbon source used for denitrification it could be a priori a promising alternative, but previous attempts to use it for EBPR have failed. This study is the first successful report of methanol utilization as external carbon source for EBPR. Since a direct replacement strategy (i.e., supply of methanol as a sole carbon source to a propionic‐fed PAO‐enriched sludge) failed, a novel process was designed and implemented successfully: development of a consortium with anaerobic biomass and polyphosphate accumulating organisms (PAOs). Methanol‐degrading acetogens were (i) selected against other anaerobic methanol degraders from an anaerobic sludge; (ii) subjected to conventional EBPR conditions (anaerobic + aerobic); and (iii) bioaugmented with PAOs. EBPR with methanol as a sole carbon source was sustained in a mid‐term basis with this procedure. Biotechnol. Bioeng. 2013; 110: 391–400. © 2012 Wiley Periodicals, Inc. Abstract : Enhanced biological phosphorus removal (EBPR) from wastewater was obtained with methanol as a sole carbon source using a syntrophic consortium of acetogens and PAO. Methanol‐degrading acetogens survive under conventional anaerobic/aerobic EPBR configuration, which favors PAO coexistence and avoids methanogenic activity. By contrast, a propionate‐fed PAO‐enriched sludge didn't survive with methanol as a sole carbon source due to the lack of acetogenic VFA production from methanol.